Potential of Endocannabinoids to Control Bladder Pain - Bjorling, Dale E.; Wang, Zun-yi (Frontiers in Systems Neuroscience, 2018)
Bladder-related pain is one of the most common forms of visceral pain, and visceral pain is among the most common complaints for which patients seek physician consultation. Despite extensive studies of visceral innervation and treatment of visceral pain, opioids remain a mainstay for management of bladder pain. Side effects associated with opioid therapy can profoundly diminish quality of life, and improved options for treatment of bladder pain remain a high priority. Endocannabinoids, primarily anandamide (AEA) and 2-arachidonoylglycerol (2-AG), are endogenously-produced fatty acid ethanolamides with that induce analgesia. Animal experiments have demonstrated that inhibition of enzymes that degrade AEA or 2-AG have the potential to prevent development of visceral and somatic pain. Although experimental results in animal models have been promising, clinical application of this approach has proven difficult. In addition to fatty acid amide hydrolase (FAAH; degrades AEA) and monacylglycerol lipase (MAGL; degrades 2-AG), cyclooxygenase (COX) acts to metabolize endocannabinoids. Another potential limitation of this strategy is that AEA activates pro-nociceptive transient receptor potential vanilloid 1 (TRPV1) channels. Dual inhibitors of FAAH and TRPV1 or FAAH and COX have been synthesized and are currently undergoing preclinical testing for efficacy in providing analgesia. Local inhibition of FAAH or MAGL within the bladder may be viable options to reduce pain associated with cystitis with fewer systemic side effects, but this has not been explored. Further investigation is required before manipulation of the endocannabinoid system can be proven as an efficacious alternative for management of bladder pain.